Comparing the effect of different surfactants on the aggregation and electrical contact properties of graphene nanoplatelets - Krittayavathananon, A; Li, X; Batchelor-McAuley, C; Sawangphruk, M; Compton, RG (Elsevier, 2018)
We report the influence of different surfactants, Triton X-100, sodium dodecyl sulfate (SDS) and cetrimonium bromide (CTAB), on the suspended graphene nanoplatelets (GNPs) in aqueous solution studied via a single entity electrochemical technique. This method simply requires recording the current responses resulting from the impacts of individual and aggregated GNPs with an interdigitated gold electrode array. Upon impact the nanomaterial can bridge across two interdigitated gold microbands creating an electrical contact. The current magnitude reflects both the agglomeration state of the material and the contact resistance between the gold array and the carbon nanomaterial. The sensitivity of the magnitude of the current steps to the identity of the used surfactant was further evidenced, indicating the influence of these surfactants upon the electrical connectivity of the nanomaterial to the electrode substrate.